WORKSHOP PEMBUATAN POSTER SEBAGAI UPAYA MENINGKATKAN KESADARAN ANTI-CYBERBULLYING PADA SISWA - I Made Sonny Gunawan; K. Dedy Sandiarsa S.; I Made Gunawan; Soemardiawan Soemardiawan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Cyberbullying has become an increasingly serious issue in schools due to the widespread use of social media among adolescents. Limited student awareness of the impacts of cyberbullying contributes to the persistence of online harassment, which may adversely affect students’ psychological well-being and academic performance. This community service program aimed to improve students’ understanding of the dangers of cyberbullying, foster empathy, and promote a safe and supportive school environment through an anti-cyberbullying poster workshop. The program was implemented with Grade 11 social science students at SMA Negeri 3 Mataram using a participatory and educational approach. Activities included preparation, educational sessions, group discussions, poster design and production, presentations, reflection, and evaluation through observations and simple questionnaires. The results indicated increased student participation, knowledge, awareness, empathy, and skills in communicating anti-cyberbullying messages through creative visual media. The posters produced during the workshop were displayed throughout the school and disseminated via the school's digital platforms as part of a continuing awareness campaign. Overall, the workshop proved to be an effective preventive strategy for strengthening digital literacy, fostering responsible social media use, and creating a safer and more positive school environment. ABSTRAK Cyberbullying menjadi salah satu permasalahan yang semakin meningkat di lingkungan sekolah seiring tingginya penggunaan media sosial oleh remaja. Rendahnya pemahaman siswa mengenai dampak cyberbullying menyebabkan perilaku perundungan digital masih sering terjadi dan berpotensi mengganggu kondisi psikologis maupun proses belajar peserta didik. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan pemahaman siswa tentang bahaya cyberbullying, menumbuhkan sikap empati, serta menciptakan lingkungan sekolah yang aman dan kondusif melalui workshop pembuatan poster anti-cyberbullying. Kegiatan dilaksanakan pada siswa kelas XI IPS SMA Negeri 3 Mataram menggunakan pendekatan partisipatif dan edukatif melalui tahapan persiapan, penyampaian materi, diskusi, praktik pembuatan poster, presentasi, refleksi, serta evaluasi menggunakan observasi dan angket sederhana. Hasil kegiatan menunjukkan meningkatnya partisipasi, pemahaman, kesadaran, sikap empati, dan keterampilan siswa dalam menyampaikan pesan pencegahan cyberbullying melalui media visual. Poster yang dihasilkan dimanfaatkan sebagai media kampanye di lingkungan sekolah dan media digital sekolah. Dengan demikian, workshop pembuatan poster efektif sebagai strategi preventif untuk memperkuat literasi digital, membangun budaya sekolah yang lebih aman, serta mendorong perilaku bertanggung jawab dalam penggunaan media sosial.